Ascites, Pleural Effusion, and Edematous Gallbladder Wall: A Rare Finding of Leptospirosis - Jagdish Kumar, K.; Hamza, Sharief; Kurthkal, Kavya; Sowmya, G. S. (Journal of Pediatric Infectious Diseases, 2016)
In children, leptospirosis is generally underdiagnosed, especially if the presentation is without jaundice. Such cases can be confused with more common illnesses such as dengue or scrub typhus in the tropical countries. Having a specific drug therapy for treatment makes the early etiological diagnosis of leptospirosis much more important. Leptospirosis may present with an atypical presentation also. Serosal surface and gallbladder wall involvement are rare in leptospirosis. We report a 12-year-old boy with leptospirosis, who presented with meningoencephalitis, thrombocytopenia, shock, and ultrasonography revealed ascites, a pleural effusion, and an edematous gallbladder wall.
Keywords: leptospirosis; ascites; pleural effusion; edematous gallbladder wall